Leukocyte immunoglobulin‐like receptor B4: A keystone in immune modulation and therapeutic target in cancer and beyond - Qi Liu; Yuyang Liu; Zhanyu Yang (Cancer Innovation)
Abstract Leukocyte immunoglobulin‐like receptor B4 (LILRB4) significantly impacts immune regulation and the pathogenesis and progression of various cancers. This review discusses LILRB4's structural attributes, expression patterns in immune cells, and molecular mechanisms in modulating immune responses. We describe the influence of LILRB4 on T cells, dendritic cells, NK cells, and macrophages, and its dual role in stimulating and suppressing immune activities. The review discusses the current research on LILRB4's involvement in acute myeloid leukemia, chronic lymphocytic leukemia, and solid tumors, such as colorectal cancer, pancreatic cancer, non‐small cell lung cancer, hepatocellular carcinoma, and extramedullary multiple myeloma. The review also describes LILRB4's role in autoimmune disorders, infectious diseases, and other conditions. We evaluate the recent advancements in targeting LILRB4 using monoclonal antibodies and peptide inhibitors and their therapeutic potential in cancer treatment. Together, these studies underscore the need for further research on LILRB4's interactions in the tumor microenvironment and highlight its importance as a therapeutic target in oncology and for future clinical innovations.